(untitled) (Research, Society and Development, 2026)
The aim of this article is to investigate and analyze CAPS users’ perceptions regarding the conditions of autonomy and how their protagonism takes place within the mental health service and in the community, as well as their participation in health care. We sought to analyze the perceptions of users about how their protagonism and autonomy take place in the spaces in which they are inserted. A qualitative social research study was conducted, having the focus group and the field diary as the main instruments of data production, analyzed through content analysis. It was evident that Mental Health users are exposed to different types of violence. Many live in regions of greater vulnerability and social risk, where they live in unhealthy places and collective rooms, such as tenements. The existing challenges to encourage user participation in the community, spaces and services in which they are inserted were discussed, awakening emancipatory processes.